Extrapyramidal Dysfunction as a Consequence of Hypoxic Brain Injury - Bayasgalan Tserensodnom; Khandsuren Baatar; Ariunaa Jambaldorj; Dariimaa Surenjav; Ichinkhorloo Manjaa (Central Asian Journal of Medical Sciences, 2017)
Objective: A case of parkinsonism after hypoxic ischemic encephalopathy is reported. Methods and Results: A 34-year-old woman presented parkinsonism due to hypoxic-anoxic encephalopathy. The manifestation of parkinsonian syndrome was more present axially, than in the limb. She has also experienced cognitive deficits. The brain Magnetic Resonance Imaging (MRI) studies have shown abnormalities in putamen, caudate nucleus, globus pallidus and cerebral cortex. Conclusions: Diversity of clinical features may be depend on different neuropathological damage and neurotransmitter disbalance within the basal ganglia after a hypoxic-ischemic arrest, as seen in our patient. Therefore, understanding of all factors that contribute hypoxic brain injury is important to determine the clinical outcome and further management of patients.